Learning Outcomes and Insights from a Chocolate-based Undergraduate Materials Science Course and Other Topical Outreach Activities. (5th January 2018) - Dailey, Jennifer
ABSTRACT: Those involved in STEM outreach, from elementary schools through undergraduate students, all use varying teaching styles in an effort to instruct and inspire students. However, it is incredibly difficult to gauge or compare learning outcomes from new teaching techniques in situ. In this work, we describe the outcomes of a new undergraduate mini-course at Johns Hopkins University, Chocolate: An Introduction to Materials Science. In particular, the outcomes of teaching binary phase diagrams in this course using topical food examples were compared to the outcomes of the same instructor teaching a similar control group of students using standard textbook examples, reducing a number of confounding factors and allowing us to objectively analyze the benefits of using an atypical, popular approach to teach a standard subject. Results indicate that the students in the Chocolate course were not only more excited and engaged in the lecture, but they had identical or potentially greater learning gains than the control group.